Graft Tensioning in Superior Capsular Reconstruction Improves Glenohumeral Joint Kinematics in Massive Irreparable Rotator Cuff Tears: A Biomechanical Study of the Influence of Superior Capsular Reconstruction on Dynamic Shoulder Abduction. Issue 10 (6th October 2020) - Dyrna, Felix; Berthold, Daniel P.; Muench, Lukas N.; Beitzel, Knut; Kia, Cameron; Obopilwe, Elifho; Pauzenberger, Leo; Adams, Christopher R.; Cote, Mark P.; Scheiderer, Bastian; Mazzocca, Augustus D.
Background: Superior capsular reconstruction (SCR) for massive, irreparable rotator cuff tears has become more widely used recently; however, ideal tensioning of the graft and the influence on joint kinematics remain unknown. Purpose/Hypothesis: The purpose of this study was to assess the effects of graft tensioning on glenohumeral joint kinematics after SCR using a dermal allograft. The hypothesis was that a graft fixed under tension would result in increased glenohumeral abduction motion and decreased cumulative deltoid forces compared with a nontensioned graft. Study Design: Controlled laboratory study. Methods: A total of 10 fresh-frozen cadaveric shoulders were tested using a dynamic shoulder simulator. Each shoulder underwent the following 4 conditions: (1) native, (2) simulated irreparable supraspinatus (SSP) tear, (3) SCR using a nontensioned acellular dermal allograft, and (4) SCR using a graft tensioned with 30 to 35 N. Mean values for maximum glenohumeral abduction and cumulative deltoid forces were recorded. The critical shoulder angle (CSA) was also assessed. Results: Native shoulders required a mean (±SE) deltoid force of 193.2 ± 45.1 N to achieve maximum glenohumeral abduction (79.8° ± 5.8°). Compared with native shoulders, abduction decreased after SSP tears by 32% (54.3° ± 13.7°; P = .04), whereas cumulative deltoid forces increased by 23% (252.1 ± 68.3 N; P = .04). The nontensioned SCR showed no significant difference in shoulder abduction (54.1° ± 16.1°) and required deltoid forces (277.8 ± 39.8 N) when compared with the SSP tear state. In contrast, a tensioned graft led to significantly improved shoulder abduction compared with the SSP tear state ( P = .04) although abduction and deltoid forces could not be restored to the native state ( P = .01). A positive correlation between CSA and maximum abduction was found for the tensioned-graft SCR state ( r = 0.685; P = .02). Conclusion: SCR using a graft fixed under tension demonstrated a significant increase in maximum shoulder abduction compared with a nontensioned graft; however, abduction remained significantly less than the intact state. The nontensioned SCR showed no significant improvement in glenohumeral kinematics compared with the SSP tear state. Clinical Relevance: Because significant improvement in shoulder function after SCR may be expected only when the graft is adequately tensioned, accurate graft measurement and adequate tension of at least 30 N should be considered during the surgical procedure. SCR with a tensioned graft may help maintain sufficient acromiohumeral distance, improve clinical outcomes, and reduce postoperative complications.